A Cybernetic Approach to Assess the Training of Manual Control Skills. Issue 19 (2016) - Pool, D.M.; Zaal, P.M.T.
Abstract: This paper presents a cybernetic approach to assess the training of manual control skills in simulators. The approach uses multi-channel pilot models that separate pilots' responses to visual and motion stimuli. This allows for a quantitative analysis of pilots' use of visual and motion cues for manual aircraft control, as well as the evolution of these control skills during training and after transfer. The cybernetic approach was applied to data from a quasi-transfer-of-training experiment performed in the SIMONA Research Simulator at Delft University of Technology. In this experiment, fully task-naive participants were trained to perform an aircraft pitch attitude tracking task in a fixed-base simulator environment. After training, participants were transferred to a motion-base simulator environment. Results indicate that the cybernetic approach is successful in revealing progressive changes in participants' utilization of visual and motion cues – i.e., their equalization dynamics – during training and after transfer. Furthermore, the results show that convergence to a final skill-based manual control strategy requires significant training.